Correlation of serum ferritin with severity of liver disease - Garyll Ryan Tariang Blah; R S Tonk (Wolters Kluwer Medknow Publications, 2023)
Background and Aim: Serum ferritin is a marker of hepatic inflammation and has been studied to predict mortality in decompensated cirrhotics. No study has been done to evaluate ferritin as an independent marker of liver disease severity. We investigated whether serum ferritin levels can be correlated with Child-Pugh and Model for End-stage Liver Disease (MELD) scores. Materials and Methods: Seventy-five patients fulfilling the criteria were included and a cross-sectional observational study was done. Results: Seventy-five patients (68 males and 7 females) were evaluated. Serum ferritin levels were found to be significantly elevated in patients having higher Child-Pugh and MELD scores and showed a significant correlation with Child-Pugh score (P = 0.001) and MELD score (P = 0.027). On univariate analysis, serum ferritin, bilirubin, international normalized ratio, ascites, and sodium were found to be significantly associated with severity of liver disease. On multivariate analysis, however, serum ferritin was not found to have a significant association with severity of liver disease. AUROC was also determined which showed that serum ferritin had relatively poor discriminative ability. Conclusion: Elevation of serum ferritin is prevalent in chronic liver disease (CLD). In patients of CLD, severity is associated with a higher serum ferritin level. In future, a study may be designed, to obtain a prognostic model in incorporating serum ferritin into MELD similar to MELD-Na scoring system.